(untitled) (Economic Journal of Nepal, 2024)
Socioeconomic development is intricately linked with women’s empowerment. This study investigates the income-generating and social work activities of mothers’ groups at the community level, based on primary survey data. It also examines societal perceptions of women following the formation of these groups. The findings reveal that mothers’ groups generate funds through compulsory savings, donations from returnees, and participation in rituals. They allocate these funds to earn interest and support income-generating initiatives. Additionally, these groups address social issues by engaging in environmental activities and taking on judicial roles in cases involving domestic violence and gambling. The involvement in these activities has enabled members to develop public speaking skills, pursue political roles, and challenge traditional gender roles within their households.